Information environment the Internet as a means of improving the efficiency of the educational process - Ulybina E. L. (Interactive science, 2019)
the concept of “cloud technologies” is considered in this article, which over the past decade has provided Internet users with great opportunities, both integrated physical resources, and various program services. The types of "cloud infrastructure" and the possibility of their use in the educational process are investigated. software services available for online learning are enumerated.
Keywords: инфраструктура; облако; облачные вычисления; облачные сервисы; модели развертывания; cloud computing; infrastructure; Online; Online; cloud; хостинг; модели обслуживания; cloud services; deployment models; service models; hosting